2012
DOI: 10.5296/jee.v3i1.1940
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Wild Fodder of Gorumara National Park in West Bengal, India

Abstract: Gorumara National Park (GNP) in Duars, West Bengal, India, has an amazing biodiversity. Understanding of interactive factors was felt necessary. The undertaken programme included flowering plant identification, diversity indices calculation, faecal excreta examination, estimation of salinity of water courses and measurement of pH of soil and water. The floral Shannon's H at 6.38644 and Shannon's E H at 0.9996, fodder species' H and E H respectively at 2.6-4.06 and at 0.92-0.96, and mammalian species H and E H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…In India 14 of the plants sampled are wild fodder plants which are Mangifera indica, Ficus benghalensis, Portulaca oleracea, Amaranthus spinosus, Lantana camara, Phoenix sylvestris, Eragrostis tenella, Imperata cylindrica and Panicum repens (Ghosh, 2012). In India Rice, maize, sorghum, napier grass (elephant grass) and banana are also used as fodder crops (ILRI, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In India 14 of the plants sampled are wild fodder plants which are Mangifera indica, Ficus benghalensis, Portulaca oleracea, Amaranthus spinosus, Lantana camara, Phoenix sylvestris, Eragrostis tenella, Imperata cylindrica and Panicum repens (Ghosh, 2012). In India Rice, maize, sorghum, napier grass (elephant grass) and banana are also used as fodder crops (ILRI, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies also indicate that grasses are the most preferred diet for rhino [21,22,23]. Similar types of findings were also observed across most Indian one-horned rhino reserves from India and Nepal [24,25]. Hence it can be opined that the rhinos are more habitat specialised than other megaherbivores and depend on food quality rather than quantity [22,26].…”
Section: Introductionmentioning
confidence: 72%
“…Results from the predictor inspection showed that the grassland cover along with its class metrics remained the top predictors in explaining the spatial distribution of all three mega-herbivores viz., Rhino, Elephant and Gaur in GNP (Fig 4). The significant influence of grassland on megaherbivores of GNP can be attributed to several studies, suggesting substantial consumption of grasses in the diet of megaherbivores, especially for rhinos [21–25]. Hence, loss of grassland habitats will be challenging for the park authorities in maintaining the long term viability of the population of mega-herbivores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, overexploitation is also responsible for sharp reduction of the population size of the fodder plants [6]. It is important to detect the food habit of the herbivores and identify the fodder plants and their interactions with animals for sustainable management of the protected areas through wildlife conservation and undisturbed breeding ground [7]. But, in Bangladesh, there is a great dearth of information and research on the wild fodder-bearing trees.…”
Section: Rationale Of the Studymentioning
confidence: 99%